Tantangan melakukan kajian literatur psikologi di Indonesia: Masalah mendasar dan solusinya - El Hafiz, Subhan; Himawan, Karel Karsten (Konsorsium Psikologi Ilmiah Nusantara, 2020)
As one of the scientific methods, literature review is distinguished by its ability to generate conclusions in the highest level of confidence as it relies on the analysis of numerous published empirical studies. Nevertheless, conducting a literature review on the Indonesian databases is challenging because there are wide ranges of synonymous variants for a conceptual terminology, which are mostly caused by the literal translations of the terminology from its English origin. This commentary paper highlights the fundamental challenge in conducting literature review studies using Indonesian published papers, particularly the challenge resulting from the abstinence of a guideline for terminology translations, and offers a strategy to mitigate the issue by emphasising the roles of psychological consortia and associations.